Modal approach to the controllability problem of distributed parameter systems - Zuyev, A.L. (Труды Института прикладной математики и механики, 2010)
This paper is devoted to the analysis of the controllability for a class of linear control systems in a Hilbert space. It is proposed to use the minimum energy control of a reduced lumped parameter system for solving the infinite dimensional steering problem approximately. Sufficient conditions of the approximate controllability are formulated for a modal representation of a flexible structure with small dissipation. Статья посвящена анализу управляемости класса линейных систем управления в гильбертовом пространстве. Для приближенного решения бесконечномерной проблемы управляемости используется управление с минимальной энергией, которое соответствует подсистеме с сосредоточенными параметрами. Предложены достаточные условия приближенной управляемости системы с модальными координатами, которая описывает колебания упругой механической модели с малой диссипацией. Статтю присвячено аналізу керованості класу лінійних систем керування в гільбертовому просторі. Для наближеного розв'язання нескінченновимірної проблеми керованості використовується керування з мінімальною енергією, що відповідає: підсистемі зі зосередженими параметрами. Запропоновано достатні умови наближеної керованості для системи з модальними координатами, що описує коливання пружної механічної моделі з малою дисипацією.